2016
DOI: 10.1111/jan.13030
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress in the emergency department

Abstract: Aim To investigate the prevalence of secondary traumatic stress among Emergency nurses in the West of Scotland and explore their experiences of this. Background Unexpected death, trauma and violence are regular occurrences that contribute to the stressful environment nurses working in the Emergency department experience. A potential consequence of repeated exposure to such stressors can be referred to as secondary traumatic stress. Design Triangulation of methods of data collection, using two distinct phases: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(90 citation statements)
references
References 24 publications
10
71
1
4
Order By: Relevance
“…Differences in report and variation in years where studies conducted might speculate using different criteria to investigate STS resulting in variation in reported findings. Variation among these findings implies that gender does not relate STS, but these findings must be interpreted cautiously for three reasons: majority of ED nurses are females [16], female nurses had higher level of stress than male nurses [36], and female nurses had higher level of compassion fatigue than male nurses [37]. These inconsistent findings caused Hensel et al to suggest the need for more research and further investigation to elucidate this relationship and the role of gender in STS [22].…”
Section: Personal Factorsmentioning
confidence: 82%
See 3 more Smart Citations
“…Differences in report and variation in years where studies conducted might speculate using different criteria to investigate STS resulting in variation in reported findings. Variation among these findings implies that gender does not relate STS, but these findings must be interpreted cautiously for three reasons: majority of ED nurses are females [16], female nurses had higher level of stress than male nurses [36], and female nurses had higher level of compassion fatigue than male nurses [37]. These inconsistent findings caused Hensel et al to suggest the need for more research and further investigation to elucidate this relationship and the role of gender in STS [22].…”
Section: Personal Factorsmentioning
confidence: 82%
“…Previous studies from different geographic areas showed that prevalence of STS of a sample of emergency nurses reported at least one symptom of STS during the time of the study, and 39% of them met the whole criteria of STS [16]. These rates are alarming and require attention of stakeholders.…”
Section: Prevalence Of Sts In Ed Nursesmentioning
confidence: 97%
See 2 more Smart Citations
“…İkincil travmatizasyon açısından ise acil servis çalışanları risk gruplarının başında değerlendirilmektedir (Morrison ve Joy, 2016;Duffy, Avalos, Dowling, 2015;Dominguez-Gomez ve Rutledge, 2009;Hyman, 2004;Figley, 2003;Salston ve Figley, 2003;Beaton ve Murphy, 1995). Diğer taraftan ikincil travmatizasyon konusu sıklıkla ruh sağlığı alanında travma mağdurlarıyla çalışan sosyal hizmet uzmanı, psikolog ve psikiyatristler için tartışılmakta (Adams, Figley, Boscarino, 2008;Bride, 2007;Creamer ve Liddle, 2005;Zimering, Munroe, Bird Gulliver, 2003;Nelson-Gardell ve Harris, 2003;Chrestman, 1999) ve bunun yanı sıra özellikle afetlerde arama kurtarma ekiplerinde yer alan itfaiyeci, dalgıç ve polis gibi çalışanlar açısından da ele alınmaktadır (Kunst ve ark., 2017;Schwartz, 2008;Hargrave, Scottt, McDowall, 2006).…”
Section: Literatüre İlişkin Bilgilerunclassified